The relationship between gadget use and sleep patterns and the incidence of obesity in adolescents - Nurjanah Nurjanah; Fatma Zulaikha; Rini Ernawati (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Adolescent obesity is an increasing public health problem influenced by lifestyle factors such as gadget use and sleep patterns. Excessive gadget use may promote sedentary behavior, while insufficient sleep can disrupt metabolic processes and increase the risk of weight gain among adolescents. Purpose: to analyze the relationship between gadget use, sleep patterns, and the incidence of obesity among adolescents. Method: This study employed a descriptive correlational design with a cross-sectional approach. The population consisted of all students in grades 7–9 at MTs Darul Ihsan and SMP Muhammadiyah 3 Samarinda. A total sampling technique was used, involving 152 respondents. Data were collected through anthropometric measurements to determine obesity status based on Body Mass Index (BMI) and self-administered questionnaires to assess gadget use duration and sleep patterns. Data analysis included univariate and bivariate analyzes using the Pearson Chi-Square test. Results: The majority of respondents were 13 years old (43.4%) and female (73.7%). Most adolescents had a high duration of gadget use (67.8%), and 50.7% experienced insufficient sleep duration (< 8 hours per day). Based on BMI measurements, 32.2% of respondents were classified as obese. Bivariate analysis showed no statistically significant relationship between gadget use and obesity (p-value = 0.075; OR = 2.020; 95% CI = 0.814–1.643). However, a statistically significant association was found between sleep patterns and obesity (p-value = 0.013; OR = 2.426; 95% CI = 0.756–1.833). Adolescents with insufficient sleep had approximately 2.4 times higher odds of being obese compared to those with normal sleep duration. Conclusion: Sleep patterns are significantly associated with obesity among adolescents, whereas gadget use does not show a statistically significant relationship. Since adolescent obesity is a multifactorial condition, comprehensive prevention strategies involving schools, healthcare providers, and families are necessary to promote healthy sleep habits and balanced lifestyles.